(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
The purpose of this study is for explaining about the cause of German interest so that causing German invaded Skandinavia, the main problem that studied here is about “how the background of German invasion to Skandinavia”. In the study using historical method that is, heuristic, source criticsm, interpretation dan historiography. German doing invasion because there is a general cause and special cause, for the general cause there is iron ore problem that is so important for german industry, and then there is an opinion from Kriegsmarine leader about military base for German to reach high sea, although German didn’t continue their interest into a next plan and German didn’t want to act first and considered as an invader, then incident Altmark happens, the incident become a special cause and as a trigger for the invasion and angered the German because their ship is attacked by England in the neutral water, because of that Hitler immediately ordered to continue the plan of invasion to Skandinavia. After few of adjustment then when the German invasion to Skandinavia started is determinated.